Noise-Assisted EMD Methods in Action - Colominas, Marcelo Alejandro (2012)
In this work we explore the capabilities of two noise-assisted EMD methods: Ensemble EMD (EEMD) and the recently proposed Complete Ensemble EMD with Adaptive Noise (CEEMDAN), to recover a pure tone embedded in dierent kinds of noise, both stationary and nonstationary. Experiments are carried out for assessing their performances with respect to the level of the added noise and the number of realizations used for averaging. The obtained results partly support empirical recommendations reported in the literature while evidencing new distinctive features. While EEMD presents quite dierent behaviors for dierent situations, CEEMDAN evidences some robustness with an almost unaected performance for the studied cases.